Development and physico-chemical analysis of value-added mango leather packed in different packaging materials - Singh, Baljor; Pandey, Vinay Kumar; Shukla, R N; Singh, Kunal; Singh, Sweta (Journal of Postharvest Technology, 2021)
The study aimed to develop mango leather and to analyze the composition while observing the shelf life. The sensory, quality, and nutritional parameters were investigated. We selected one variety of mango (Lal patta) with one stage of ripeness (i.e., ripe mango). Also, the product was developed with the addition of the mango pulp, sugar, honey, milk powder, coconut powder, and potassium meta bisulfate. 4 samples (A, B, C, and D) were kept at 70°C for 10 hours in a tray dryer and these samples were compared to each other. We used these additives for enhancing the vitamin-A, vitamin-C, and carbohydrate content in mango leather. All statistical analyses showed that Physico-chemical properties were different in different variety and stages of ripeness. Sensory, texture and chemical analysis showed that the quality of mango leather was satisfactory with a high amount of nutrients. The statistical analysis of the consumer’s preference showed that all the developed products were equally acceptable and sample B secured the highest score. The other products were also liked moderately as far as overall acceptability is concerned. The mango leather was stored in HDPE and LDPE bags but the best quality of mango leather was achieved in HDPE during the 60 days of storage.